Diet quality, diet-related factors and disability status among male adults of reproductive age in the USA - Andrea L Deierlein; Jaqueline Litvak; Chang Liu; Cheryl R Stein (Cambridge University Press, 2023)
Abstract Objective: To examine diet quality and diet-related factors among male adults of reproductive age with and without disabilities. Design: Cross-sectional data from the National Health and Nutrition Examination Surveys, 2013-2018. Setting: Disability was reported as serious difficulty hearing, seeing, concentrating, walking, dressing and/or running errands due to physical, mental or emotional conditions. Diet quality was assessed by the Healthy Eating Index (HEI)-2015 and diet-related factors included self-rated diet healthfulness, food security and food assistance programmes. Multivariable linear regression estimated differences in HEI-2015 scores. Multivariable Poisson regression estimated adjusted prevalence ratios (aPR) and 95 % CI for diet-related factors. Participants: In total, 3249 males, 18-44 years; of whom, 441 (13·4 %) reported having disabilities. Results: Compared with males without disabilities, those with disabilities had a 2·69-point (95 % CI: -4·18, -1·20) lower mean total HEI-2015 score and approximately one-third to half of a point lower HEI-2015 component scores for greens and beans, total protein foods, seafood and plant proteins, fatty acids and added sugars. Males with any disabilities were more likely to have low food security (aPR = 1·57; 95 % CI: 1·28, 2·92); household participation in food assistance programmes (aPR = 1·61; 95 % CI: 1·34, 1·93) and consume fast food meals during the previous week (1-3 meals: aPR = 1·11; 95 % CI: 1·01-1·21 and 4 or more meals: aPR = 1·18; 95 % CI: 1·01-1·38) compared with males with no disabilities. Conclusions: Factors affecting diet and other modifiable health behaviours among male adults of reproductive age with disabilities require further investigation. Health promotion strategies that are adaptive to diverse populations within the disability community are needed.